A structured and systematic model-based development method for automotive systems, considering the OEM/supplier interface. (February 2017) - Beckers, Kristian; Côté, Isabelle; Frese, Thomas; Hatebur, Denis; Heisel, Maritta
Abstract: The released ISO 26262 standard for automotive systems requires to create a hazard analysis and risk assessment and to create safety goals, to break down these safety goals into functional safety requirements in the functional safety concept, to specify technical safety requirements in the safety requirements specification, and to perform several validation and verification activities. Experience shows that the definition of technical safety requirements and the planning and execution of validation and verification activities has to be done jointly by OEMs and suppliers. In this paper, we present a structured and model-based safety development approach for automotive systems. The different steps are based on Jackson's requirement engineering. The elements are represented by UML notation extended with stereotypes. The UML model enables a rigorous validation of several constraints. We make use of the results of previously published work to be able to focus on the OEM/supplier interface. We illustrate our method using a three-wheeled-tilting control system (3WTC) as running example and case study. Abstract : Highlights: Break down functional safety requirements into technical safety requirements. Perform a hardware metric breakdown. Ensure completeness of the requirements by using tables with predefined cells. Define the interface to the suppliers and address functional safety.